Conjugated Block Copolymers as Model Systems to Examine Mechanisms of Charge Generation in Donor–Acceptor Materials. (14th November 2018) - Aplan, Melissa P.; Grieco, Christopher; Lee, Youngmin; Munro, Jason M.; Lee, Wonho; Gray, Jennifer L.; Seibers, Zach D.; Kuei, Brooke; Litofsky, Joshua H.; Kilbey, S. Michael; Wang, Qing; Dabo, Ismaila; et al.
Abstract: Fully conjugated donor–acceptor block copolymers are established as model systems to elucidate fundamental mechanisms of photocurrent generation in organic photovoltaics. Using analysis of steady‐state photoluminescence quenching, exciton dissociation to a charge transfer state within individual block copolymer chains is quantified. By making a small adjustment to the conjugated backbone, the electronic properties are altered enough to disrupt charge transfer almost entirely. Strong intermolecular coupling of the electron donor is introduced by synthesizing block copolymer nanoparticles. Transient absorption spectroscopy is used to monitor charge generation in block copolymer isolated chains and nanoparticles. While efficient charge transfer is observed in isolated chains, there is no indication of complete charge separation. In the nanoparticles, long‐lived polarons are observed as early as ≈15 ns. Thus, aggregation of electron donors can facilitate efficient charge generation. Abstract : Conjugated block copolymers are established as model systems to examine fundamental photophysics in organic donor–acceptor materials. Intramolecular charge transfer within isolated block copolymer chains is quantified. Block copolymer nanoparticles are synthesized to examine the effect of polymer donor aggregation on charge generation. While charge transfer is observed in isolated chains, charge‐separated states are observed only in block copolymer nanoparticles.